2018
DOI: 10.1002/nau.23505
|View full text |Cite
|
Sign up to set email alerts
|

Administration of leuprolide acetate, a GnRH agonist, improves urodynamic parameters in ovariectomized rats

Abstract: the results suggest that systemic application of LA can improve bladder dysfunction in castrated rats, and perhaps considered as a treatment for overactive bladder conditions secondary to menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…Also, previous studies suggested that OVX can cause a decreased of blood flow around the bladder neck and urethra, mucosal and smooth muscle atrophy, increased collagen synthesis and distribution, and reduced contractility. We found that the contraction induced by the muscarinic receptor agonist carbachol was significantly reduced in the detrusor muscle strips of OVX rats, consistent with previous studies (2,5,7,23). Ach and ATP are the main neurotransmitters that contract the detrusor muscle.…”
Section: Author Contributionssupporting
confidence: 92%
See 3 more Smart Citations
“…Also, previous studies suggested that OVX can cause a decreased of blood flow around the bladder neck and urethra, mucosal and smooth muscle atrophy, increased collagen synthesis and distribution, and reduced contractility. We found that the contraction induced by the muscarinic receptor agonist carbachol was significantly reduced in the detrusor muscle strips of OVX rats, consistent with previous studies (2,5,7,23). Ach and ATP are the main neurotransmitters that contract the detrusor muscle.…”
Section: Author Contributionssupporting
confidence: 92%
“…Hale as increased frequency, incontinence, urgency and nocturia. The relationship between overactive bladder and menopause is not clear but the decrease in ovarian hormones affect both in muscle fibers and innervation of bladder tissue (5). Ovariectomy causes bladder mucosa and detrusor smooth muscle atrophy, reduced blood flow, decreased bladder compliance and contractility (20,21).…”
Section: Author Contributionsmentioning
confidence: 99%
See 2 more Smart Citations